PERUBAHAN TRADISI PERKAWINAN MASYARAKAT MINANGKABAU DI DESA KAYU ARO KECAMATAN GUNUNG TALANG KABUPATEN SOLOK - Siska Puspita Sari; Bedriati Ibrahim; Tugiman Tugiman (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: Marriage Traditions Minangkabau communities in Aro Kayu village vary greatly depending on their respective regions. This can be seen from the time of release, procedures, and equipment. These differences are strongly influenced by the place of residence and the social environment and the influence of technological developments. The implementation of the marriage tradition of the Minangkabau people in Kayu Aro Solok District uses the Minangkabau customs. The purpose of this study is (1) To find out the process of implementing the Minangkabau marriage tradition in Kayu Aro village. (2) To find out the forms of changes that occur in the Minangkabau adat marriage tradition in Kayu Aro village. (3) To find out what factors influence the change in the marriage tradition of the Minangkabau people in Kayu Aro village. The research method used in this study is qualitative. The result of the research is that the process of the marriage tradition of the Minangkabau people is still being carried out. But there are several stages that have undergone changes. The stages of change are merisik and traditional wedding attire. Based on the results of interviews with the people in Aro village, the factors that cause changes in the marriage tradition of the Minangkabau people in Kayu Aro Village, Gunung Talang District, Solok Regency are technological factors and globalization factors. Key Words: Tradition, Marriage of the Minangkabau Community